Comparison of safflower oil extraction kinetics at two characteristic moisture conditions: Statistical analysis of non-linear model parameters - Baumler, Erica Raquel (2013)
In this study the kinetics of oil extraction from partially dehulled safflower seeds at two moisture conditions (7 and 9% dry basis) was investigated. The extraction essays were performed using a stirred batch system, thermostated at 50 ºC, using n-hexane as solvent. The data obtained were fitted to a modified diffusion model in order to represent the extraction kinetics. The model took into account a washing and a diffusive step. Fitting parameters were compared statistically at both moisture conditions. The oil yield was increased in the extraction time in both cases, although the oil was released at different rates. A comparison of the parameters showed that both the extracted portion in the washing phase and the effective diffusion coefficient were moisture-dependent. The effective diffusivity was 2.81 10-12 and 8.06 10-13 m2 s-1 for a moisture content of 7% and 9%, respectively.